Low-supercooling-degree settable composite phase change material, preparation method thereof and application of low-supercooling-degree settable composite phase change material in heat energy storage technology

By mixing expandable graphite with erythritol and mannitol, a low-subcoolable shaped composite phase change material was prepared, which solved the problems of amorphous, low crystallization temperature and large supercooling when the sugar alcohol phase change material was melted, and improved the heat energy release performance and the maintenance of material shape were achieved.

CN119614157APending Publication Date: 2025-03-14HEILONGJIANG UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411798715.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The sugar alcohol phase change material is in an amorphous liquid state when melted, with low crystallization temperature and high supercooling degree, resulting in unfavorable heat release.

Method used

Low supercooling fixed-shaped composite phase change material is prepared by calcining expandable graphite and mixing with erythritol and mannitol. The method includes calcining expandable graphite, dispersing ultrasonic with anhydrous ethanol, adding deionized water, erythritol powder and mannitol powder, stirring, ultrasonic, drying and grinding to obtain a composite phase change material powder.

Benefits of technology

The supercooling degree of erythritol was successfully reduced, its crystallization temperature was improved, the heat energy release performance was improved, and the shape of the material was maintained, enhancing its application capabilities in thermal energy storage technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119614157A_ABST
    Figure CN119614157A_ABST
Patent Text Reader

Abstract

The invention relates to a low-supercooling-degree settable composite phase change material and a preparation method and application thereof in a heat energy storage technology. The invention belongs to the field of phase change energy storage materials. The problems that the sugar alcohol phase change material is in an amorphous liquid state during melting, the crystallization temperature is low and the degree of supercooling is high are solved. The low-supercooling-degree settable composite phase change material disclosed by the invention is prepared from expanded graphite, erythritol powder and mannitol powder according to a reasonable ratio. The prepared composite phase change material improves the crystallization temperature, reduces the degree of supercooling, is good in shaping state after a high-temperature test, is simple in preparation process, convenient to operate, short in preparation period, simple and harmless in preparation process, and beneficial to industrial production, and the raw materials are safe, non-toxic and low in price. And the method has remarkable social benefits and economic benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of phase change energy storage materials, and in particular relates to a low supercooling shapeable composite phase change material and a preparation method thereof and an application thereof in thermal energy storage technology. Background Art

[0002] Thermal energy storage technology is a technology that stores thermal energy by heating or cooling storage media. It has broad application prospects in the fields of solar energy, "peak shifting and valley filling" of electricity, and recycling of industrial waste heat. Thermal energy storage technology mainly includes sensible heat storage technology, latent heat storage technology, and chemical reaction heat storage technology. Among them, latent heat storage technology has high research value in the field of thermal energy storage due to its advantages such as high energy storage density, small temperature fluctuation, wide application range and good thermal stability. Phase change energy storage materials are key materials used in latent heat energy storage technology. Phase change energy storage materials refer to materials with high energy storage density, large phase change latent heat, reasonable phase change temperature and low price when phase change occurs. Phase change refers to the change between two states of a substance. The phase change process can be isothermal or approximately isothermal. During the phase change process, energy absorption or release will occur. The phase change latent heat is the energy released or absorbed by the substance during the phase change process.

[0003] Sugar alcohol phase change materials have the advantages of high thermal energy storage density, low price, non-toxicity, and non-corrosiveness, and have good application prospects in the field of thermal energy storage. Erythritol has a melting temperature of about 118°C and a crystallization temperature of 16.4°C. It has a very high phase change enthalpy and is a phase change heat storage material with great application prospects. However, erythritol has a very high phase change enthalpy during the melting process and a low crystallization temperature, which is not conducive to the release of heat energy. Summary of the invention

[0004] The purpose of the present invention is to solve the problems that the sugar alcohol phase change material is in an amorphous liquid state when melted, has a low crystallization temperature and a large degree of supercooling. The present invention provides a low-supercooling shapeable composite phase change material and a preparation method thereof and an application in thermal energy storage technology.

[0005] The technical solution of the present invention is as follows:

[0006] One of the purposes of the present invention is to provide a method for preparing a low supercooling shape-setting composite phase change material, the method comprising:

[0007] S1: calcining expandable graphite to obtain expanded graphite, adding anhydrous ethanol, and ultrasonically dispersing to obtain an expanded graphite mixed solution;

[0008] S2: Add deionized water, erythritol powder and mannitol powder to the mixed solution of S1, stir evenly, perform ultrasonication, dry and grind to obtain a low supercooling shape-fixable composite phase change material powder.

[0009] It is further defined that the expandable graphite in S1 is 50 mesh.

[0010] It is further defined that the calcination temperature in S1 is 800-1200° C., and the calcination time is 20-60 s.

[0011] It is further defined that the ultrasound time in S1 is 2 to 3 hours.

[0012] It is further defined that the mass ratio of expanded graphite, erythritol powder and mannitol powder in S1 is 0.3-0.8:3-4:4-5.

[0013] It is further defined that the stirring time in S2 is 20 to 40 minutes.

[0014] It is further defined that the ultrasonic temperature in S2 is 70-90° C., and the ultrasonic time is 1-2 h.

[0015] It is further defined that the grinding time in S2 is 15 to 20 minutes.

[0016] The second object of the present invention is to provide a low supercooling shape-setting composite phase change material prepared by the above preparation method.

[0017] The third object of the present invention is to provide an application of the above-mentioned low supercooling shapeable composite phase change material in thermal energy storage technology.

[0018] Compared with the prior art, the specific advantages of the present invention are as follows:

[0019] (1) The erythritol and mannitol selected by the present invention have strong practical applicability in medium-temperature phase change energy storage. Mannitol has the advantages of high phase change enthalpy and high crystallization temperature, which can improve the defect of low crystallization temperature of erythritol, which is not conducive to the release of heat energy. The present invention mixes erythritol and mannitol to prepare a composite phase change material, which proves that mannitol can increase the crystallization temperature of erythritol.

[0020] (2) The expandable graphite selected by the present invention is calcined to prepare expanded graphite, which has affinity for organic materials and polymers. Its interior is composed of a large number of composite pores with diameters in the nanometer and micrometer levels. It has stable chemical properties, light weight and low density, and high thermal conductivity. It is an excellent material for enhancing the heat transfer of phase change materials.

[0021] (3) The sugar alcohol selected by the present invention is food grade, safe, non-toxic and inexpensive, with a short preparation cycle, a simple preparation process and no harm; the erythritol and mannitol selected by the present invention as phase change materials have the advantages of large phase change enthalpy value and wide phase change temperature range, and expanded graphite is used as a reinforcement, which can not only increase the crystallization temperature of the erythritol and mannitol composite phase change material, but also maintain the shape of the erythritol and mannitol composite phase change material; the present invention has good applicability, and the crystallization properties of the obtained composite phase change material will vary due to different contents of expanded graphite, erythritol and mannitol, which can meet the preparation of materials with different needs. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 a is a scanning electron microscope image of expanded graphite of Example 2, Figure 1 b is a scanning electron microscope image of expanded graphite after ultrasonic dispersion in Example 2;

[0023] Figure 2 a Melting curve diagram of Examples 1-3 and Comparative Examples 1-2, Figure 2 b is the crystallization curve diagram of Example 1-3 and Comparative Example 1-2;

[0024] Figure 3 a is the melting curve diagram of Comparative Example 3-5, Figure 3 b is the crystallization curve diagram of Comparative Example 3-5;

[0025] Figure 4 It is a test chart of the shaping ability of Examples 1-3 and Comparative Examples 1-2. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0027] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.

[0028] Embodiment 1:

[0029] S1: calcining 3 g of 50-mesh expandable graphite in a muffle furnace at 900°C for 45 seconds to obtain expanded graphite, dispersing 0.423 g of expanded graphite in 150 ml of anhydrous ethanol, and ultrasonicating for 2 hours to obtain an expanded graphite mixed solution;

[0030] S2: Add 50 mL of deionized water, 3.663 g of erythritol powder and 4.372 g of mannitol powder to the mixed solution of S1, stir for 30 min, ultrasonicate at 80 °C for 2 h, dry at 60 °C, and grind for 15 min to obtain a low supercooling shape-setting composite phase change material powder.

[0031] Embodiment 2:

[0032] The difference between Example 2 and Example 1 is that the amount of expanded graphite in S1 is 0.605 g, and the other steps are the same as those in Example 1.

[0033] Embodiment 3:

[0034] The difference between Example 3 and Example 1 is that the amount of expanded graphite in S1 is 0.795 g, and the other steps are the same as those in Example 1.

[0035] Comparative Example 1:

[0036] The difference between Comparative Example 1 and Example 1 is that the anhydrous ethanol in S1 is 100 mL, the expanded graphite is 0.249 g, and the other steps are the same as those in Example 1.

[0037] Comparative Example 2:

[0038] The difference between Comparative Example 2 and Example 1 is that the anhydrous ethanol in S1 is 100 mL, the expanded graphite is 0.081 g, and the other steps are the same as those in Example 1.

[0039] Comparative Example 3:

[0040] S1: calcining 3 g of 50-mesh expandable graphite in a muffle furnace at 900°C for 45 seconds to obtain expanded graphite, dispersing 0.301 g of expanded graphite in 100 ml of anhydrous ethanol, and ultrasonicating for 2 hours to obtain an expanded graphite mixed solution;

[0041] S2: Add 50 mL of deionized water and 4 g of erythritol powder to the mixed solution of S1, stir for 30 min, ultrasonicate at 80 °C for 1 h, dry at 60 °C, and grind for 15 min to obtain phase change material powder.

[0042] Comparative Example 4:

[0043] S1: calcining 3 g of 50-mesh expandable graphite in a muffle furnace at 900°C for 45 seconds to obtain expanded graphite, dispersing 0.301 g of expanded graphite in 100 ml of anhydrous ethanol, and ultrasonicating for 2 hours to obtain an expanded graphite mixed solution;

[0044] S2: Add 50 mL of deionized water and 4 g of mannitol powder to the mixed solution of S1, stir for 30 min, ultrasonicate at 80 °C for 1 h, dry at 60 °C, and grind for 15 min to obtain phase change material powder.

[0045] Comparative Example 5:

[0046] Take 50 mL of deionized water, add 3.663 g of erythritol powder and 4.372 g of mannitol powder, stir for 30 min, ultrasonicate at 80 ° C for 2 h, dry at 60 ° C, and grind for 15 min to obtain a phase change material.

[0047] Differential scanning calorimetry (DSC) was used to measure the melting and crystallization data of the composite phase change material, and an electric heating vacuum drying oven was used to measure the shape-setting ability of the composite phase change material. The melting and crystallization parameters of the composite phase change material are specifically shown in Table 1.

[0048] Table 1 Melt crystallization parameters of composite phase change materials, erythritol and mannitol of Examples 1-3 and Comparative Examples 1-5

[0049]

[0050] From Table 1, we can see that the supercooling of Example 1, Example 2 and Example 3 is less than 21°C, which proves that the present invention successfully reduces the supercooling of erythritol. This is because there are 4 hydroxyl groups in the molecular structure of erythritol. The interaction between these hydroxyl groups may make it difficult for the molecules to form a stable crystal arrangement. The ability of erythritol itself to form crystals is relatively weak. When erythritol melts with increasing temperature, the molecules are no longer arranged neatly, the crystal structure begins to be destroyed, and it is difficult to form a new structure. Mannitol has excellent crystallization performance. After mixing erythritol with mannitol, mannitol crystallizes first. Erythritol can adhere to mannitol nodules and crystallize, and the crystallization performance of erythritol is improved. Expanded graphite is added to the erythritol / mannitol composite phase change material after ultrasonic dispersion, which increases the thermal conductivity of the composite phase change material, is conducive to the internal heat diffusion and accelerates the crystallization of the phase change material. At the same time, erythritol and mannitol can adhere to expanded graphite crystallization, which greatly reduces the supercooling.

[0051] Expanded graphite has two main functions in the present invention. One is that the high thermal conductivity of expanded graphite is conducive to the internal heat diffusion of the composite phase change material and is conducive to increasing the crystallization temperature of the composite material. Figure 2 b and Figure 3It can be seen from the crystallization curve of b that compared with other comparative examples and embodiments of composite phase change materials with added expanded graphite, comparative example 5 has a gentle crystallization peak and no significant increase in crystallization temperature, while the comparative examples and embodiments with added expanded graphite have sharper crystallization peaks and significantly increased crystallization temperatures; another is that the three-dimensional structure of expanded graphite is conducive to the shaping of the composite phase change material. The embodiment of the present invention is a composite phase change material prepared by expanding graphite, erythritol and mannitol. The supercooling degree is lower than that of the composite phase change material prepared by expanding graphite and erythritol in comparative example 3 and the composite phase change material prepared by expanding graphite and mannitol in comparative example 4, and is also lower than that of comparative examples 1 and 2 in which the composite phase change materials are prepared by expanding graphite, erythritol and mannitol. This is because erythritol and mannitol together as phase change matrix materials have a wider heat absorption and release temperature range than a single sugar alcohol as a phase change matrix material, while the proportion of expanded graphite in comparative examples 1 and 2 is small and is not within the protection scope of the present invention. The three-dimensional skeleton formed by expanded graphite inside the composite phase change material is unstable, and flows as the sugar alcohol melts and heats up, so the supercooling degree will be high and the shaping ability is poor.

[0052] Composite phase change material shaping ability test:

[0053] Test method: An electric vacuum drying oven is used to determine the shaping ability of the composite phase change material. 0.4 g of the phase change material powder of Examples 1-3 and Comparative Examples 1-2 are respectively put into a tablet pressing mold, the pressure is set to 16 MPa, the pressure holding time is 3 min, and the round slices are pressed. The temperature of the vacuum drying oven is set to 185°C, and the round slices pressed by Examples 1-3 and Comparative Examples 1-2 are placed therein, kept warm for 30 min, the samples are taken out and cooled naturally, and the shape of the samples is observed to see if there is any change.

[0054] pass Figure 4 We can see that after the shaping ability test, the shapes of the materials of Examples 1-3 did not change, and the shaping performance was excellent, while after the shaping ability test, the shapes of Comparative Examples 1 and 2 changed, and the shaping performance was poor, indicating that the technical solution of the present invention successfully prepared a shapeable composite phase change material.

[0055] The above are only preferred specific embodiments of the present invention, which are all different implementations based on the overall concept of the present invention, and the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for preparing a low supercooling shape-setting composite phase change material, characterized in that: The method: S1: calcining expandable graphite to obtain expanded graphite, adding anhydrous ethanol, and ultrasonically dispersing to obtain an expanded graphite mixed solution; S2: Add deionized water, erythritol powder and mannitol powder to the mixed solution of S1, stir evenly, perform ultrasonication, dry and grind to obtain a low supercooling shape-fixable composite phase change material powder.

2. The method according to claim 1, characterized in that The expandable graphite in S1 is 50 mesh.

3. The method according to claim 1, characterized in that In S1, the calcination temperature is 800-1200°C, and the calcination time is 20-60s.

4. The method according to claim 1, characterized in that: The ultrasound time in S1 is 2 to 3 hours.

5. The method according to claim 1, characterized in that The mass ratio of expanded graphite, erythritol powder and mannitol powder in S1 is 0.3-0.8:3-4:4-5.

6. The method according to claim 1, characterized in that The stirring time in S2 is 20 to 40 minutes.

7. The method according to claim 1, characterized in that The ultrasonic temperature in S2 is 70-90°C, and the ultrasonic time is 1-2h.

8. The method according to claim 1, characterized in that The grinding time in S2 is 15 to 20 minutes.

9. A low supercooling shapeable composite phase change material, characterized in that: Prepared by the method according to any one of claims 1 to 8.

10. Application of the low undercooling shape-setting composite phase change material according to claim 9 in thermal energy storage technology.

Citation Information

Patent Citations

  • High thermal conductivity medium temperature form-stable phase change material and preparation method thereof

    CN104845592A

  • Preparation of molded expanded graphite-based erythritol medium-temperature composite phase change heat storage material

    CN107603571A

  • High-phase-change latent heat composite material and preparation method thereof

    CN111978928A

  • Preparation method of erythritol expanded graphite high-thermal-conductivity shaped composite phase change material

    CN118580838A